Counseling preadolescent bullies through cognitive behavioral strategies - Angeles, Ludeth Zyra P. (College of Education, University of the Philippines Diliman, 2018)
The present study was designed to examine the effectiveness of cognitive behavioral strategies in reducing aggressive behaviors of identified bullies among neglected, abandoned, and orphaned children in a residential care. There were 19 male preadolescents aged eight to 12 years who participated in the focus group discussions and ten identified bullies who participated in the group counseling sessions. One of the most significant findings to emerge from this study is that bullies have different irrational thoughts particularly that they must have control over others, should gain the approval and be liked by others, and must protect themselves from being the target of bullying. The second finding showed that perpetrators would typically impose harm through direct and indirect manners as reported by the identified bullied and house parents. Conversely, the identified bullies merely pointed out that direct form of bullying is the common bullying behavior displayed by perpetrators so as to directly show their strength and power. This study also indicated that the group counseling intervention was not effective based on the pre and post observation of the house parents and the researcher. Using the Wilcoxon Signed Rank test, the study also found out that there were varying findings on the use of counseling intervention using cognitive behavioral strategies. Results imply that the aggression scores of the participants were significantly decreased based on self-rating (Z = -1.472, p < .05) but no significant reduction in aggression based on the report of house parents (Z = - 2.111, p > .05) after the group counseling sessions. The findings of this study are less generalizable to evaluate the efficacy of the Cognitive Behavioral Strategies because of the small sample size, different perceptions of house parents and social desirability of the participants.